Credit chain and sectoral comovement: A multi-region investigation - Hsiao-Hui Lee; S. Alex Yang; Yuxuan Zhang; Kijin Kim (Asian Development Bank (ADB), 2021)
This paper empirically examines how sectoral comovements are correlated with trade credit usage in a multi-region setting. Extending the models in Shea (2002) and Raddatz (2010), we develop a framework that captures the impact of trade credit usage on comovement between sectors within an economy and across economies separately. Using the Multi-Regional Input-Output Table developed by the Asian Development Bank, we assemble a dataset consisting of 14 manufacturing industries for 53 economies. We provide empirical evidence that trade credit linkage is an influential channel for both the domestic and cross-border shocks to propagate and create a more profound impact on industries around the globe. We find that the impact of domestic credit chains on sectoral comovement is twice as strong as that of the international ones. We further examine the time trend of this relationship and find that, from 2000 to 2018, the positive relationship between the intensity of trade credit usage and sectoral correlation decreases. We posit that this could be due to more diversified global trade pattern changes during these two decades.
Keywords: E32; G29; G32; 330; trade credit; credit chain; sectoral comovement; input-output table; systemic risk